The relationship between species diversity and functional diversity along aridity gradients in semi-arid rangeland. (December 2021) - Dovrat, Guy; Meron, Ehud; Shachak, Moshe; Moshe, Yosef; Osem, Yagil
Abstract: The relationship between community species diversity and functional diversity (SFDR) was suggested to reflect the degree of overlap in species functions and highlight the effects of environmental filters on community composition. Using a novel approach, categorizing individual plants into functional groups according to their plant biomass production (function level) and regardless of their taxonomic attribution, we tested the pattern of SFDR (e.g., linear correlation or other type) in a semiarid, annual plant community. Species abundance and biomass were monitored over four years among neighbouring topographic sites representing a range of aridity levels in the Northern Negev, Israel. All sampled plant individuals collected at flowering season were weighted and classified into ten functional groups according to their above-ground biomass. Functional group richness and species richness were calculated for each of the 16 research plots during the four research years. We examined the relationship between species richness and functional richness and the effects of year and topographic site on species richness within each of the functional groups. Species and functional richness varied considerably among years and topographic sites. Functional richness was found to be positively related to species richness throughout the entire studied aridity range. Under relatively humid conditions, species richness was high, and increasing aridity led mainly to loss of functional redundancy. Lost taxa were typically rare, large sized or drought intolerant species with low functional plasticity. Conversely, under relatively dry conditions, species richness was low and further increasing aridity led more to loss of functional richness than to loss of species richness. Typical species that drove this pattern were abundant, medium to low sized and drought tolerant species with high functional plasticity. These species decreased their plant biomass production while guaranteeing their existence under extreme drought. Highlights: Species and functional richness varied considerably among years and sites Functional richness was positively related to species richness The positive relationship held over the entire range of environmental conditions Under humid conditions, increasing drought led to loss of functional redundancy Under dry conditions, increasing drought led mainly to loss of function-levels